Analysis of the Application of Grammar and Sentence Structure by Native English Speakers in English Talk Show, Sitcom, and Vlog on the YouTube Platform - Moehamad Ridhwan; Sri Gustiani; Risnawati; Herman (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
ABSTRACT: This study was aimed to evaluate two contrasting perspectives on learning English. The first perspective suggests that learning grammar is not too important to be able to speak English. It argues that since native English speakers do not consciously follow grammar rules, learners should focus on speaking practice instead of worrying about grammar. The second perspective argues that the importance of learning grammar is to construct proper sentences in conversations. It believes that mastering grammar is essential for effectively learning English and that excluding grammar makes learning the language impossible. To evaluate these viewpoints, informal conversations and a monologue by three purposively selected native English speakers from an English Talk Show, Sitcom, and Vlog on YouTube were analysed using a thematic analysis. The data were collected through a combination of non-participant and structured observations. The findings revealed that, contrary to the first perspective, native English speakers consistently use proper grammar, even in informal contexts.   Keywords: English Talk show, Grammar and Structure Usage, Sitcom, Vlog